Low-dose rivaroxaban and aspirin among patients with peripheral artery disease: a meta-analysis of the COMPASS and VOYAGER trials. (31st August 2021) - Anand, Sonia S; Hiatt, Will; Dyal, Leanne; Bauersachs, Rupert; Berkowitz, Scott D; Branch, Kelley R H; Debus, Sebastian; Fox, Keith A A; Liang, Yan; Muehlhofer, Eva; Nehler, Mark; Haskell, Lloyd P; et al.
Abstract: Aims: Peripheral artery disease (PAD) patients suffer a high risk of major cardiovascular (CV) events, with athero-thrombo-embolism as the underlying pathophysiologic mechanism. Recently, two large randomized clinical trials evaluated the efficacy and safety of low-dose rivaroxaban twice daily plus aspirin in stable PAD outpatients and those immediately after peripheral revascularization. We sought to determine if the effects of low-dose rivaroxaban and aspirin compared to aspirin alone are consistent across this broad spectrum of PAD patients. Methods and results: We conducted a random-effects meta-analysis of the COMPASS and VOYAGER randomized trials among 11 560 PAD patients (4996 from COMPASS and 6564 from VOYAGER) in the primary analysis and 9332 (2768 from COMPASS and 6564 from VOYAGER) with lower extremity (LE)-PAD in the secondary analysis. The hazard ratio (HR) for the composite of CV death, myocardial infarction, ischaemic stroke, acute limb ischaemia, or major vascular amputation was 0.79 (95% confidence interval, CI: 0.65–0.95) comparing low-dose rivaroxaban plus aspirin to aspirin alone. While the risk of major bleeding was increased with low-dose rivaroxaban plus aspirin compared to aspirin alone [HR: 1.51 (95% CI: 1.22–1.87)], there was no significant increase in severe bleeding [HR: 1.18 (95% CI: 0.79–1.76)]. Similar effects were observed in the subset with symptomatic LE-PAD. Conclusions: Among PAD patients, low-dose rivaroxaban plus aspirin is superior to aspirin alone in reducing CV and limb outcomes including acute limb ischaemia and major vascular amputation. This reduction is offset by a relative increase in major bleeding, but not by an excess of fatal or critical organ bleeding. The consistency of findings of these trials supports the use of combination low-dose rivaroxaban plus aspirin in PAD patients across a broad spectrum of disease.